Edukasi Kepatuhan Obat dan Diet Rendah Garam pada Pasien Hipertensi di Ruang Penyakit Dalam Pria RSUD Jayapura - Sumiyati, Sumiyati; Ambarika, Rahmania (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Hypertension is a non-communicable disease that remains a major public health problem in Indonesia. The prevalence of hypertension among adults aged 18 years and over reaches 34.1%, with most cases being asymptomatic yet potentially leading to serious complications such as stroke, kidney failure, and heart disease. This situation underscores the need for effective health education to control risk factors by improving patient adherence to antihypertensive medication and a low-salt diet. Objective: This community service activity aimed to improve patients’ knowledge, awareness, and adherence to antihypertensive therapy and the implementation of a low-salt diet to maintain optimal blood pressure control. Method: The program was carried out in the Internal Medicine Ward of RSUD Jayapura using direct health education and outreach methods with printed leaflets as educational media. This approach was chosen because it enables practical, clear, and direct communication of health information to patients and families. Leaflets also allow patients to review the material independently at home. Result: The results showed a notable increase in patients’ and families’ understanding after participating in the educational activity. Post-education assessments indicated improved knowledge and awareness regarding medication adherence and dietary salt restriction. The leaflet proved to be an effective, easy-to-understand, and practical educational medium for supporting sustainable health promotion among hypertensive patients. Conclusion: Health education through printed leaflets can effectively increase patient knowledge and adherence to antihypertensive medication and a low-salt diet. This medium supports healthcare workers in delivering consistent and continuous patient education for better hypertension management outcomes.